Cultural adaptation of CBT for serious mental illness : a guide for training and practice - Rathod, Shanaya; Kingdon, David G.; Pinninti, Narsimha; Turkington, Douglas; Phiri, Peter (Chichester, West Sussex ; Malden, MA : Wiley Blackwell, 2015)
"This book is designed to enable CBT clinicians to engage people from diverse cultural backgrounds by adapting their therapeutic techniques, resulting in increased therapist confidence and much improved patient outcomes"--Provided by publisher.
Epidemiology of Psychosis and CultureCulture and the Aetiology of Psychosis; Philosophical Orientation and Theoretical Considerations; Practical Considerations; Technical Adjustments and Theoretical Modifications; Conclusion; References; 9 Depression; Philosophical Orientation and Practical Considerations; Technical Adjustments and Theoretical Modifications; Conclusion; References; 10 Bipolar Affective Disorder; Philosophical Orientation and Practical Considerations; Technical Adjustments and Theoretical Modifications; Conclusion; References
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cognitive therapy -- Methodology; Cultural pluralism; Mental illness -- Treatment; Cognitive Therapy -- methods; Cultural Diversity; Mental Disorders -- therapy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Cognitive therapy -- Methodology; Cultural pluralism; Mental illness -- Treatment; Electronic books